Scooby-Doo in Arabian nights [videorecording (DVD)] - Romersa, Joanna; Falkenstein, Jun; Kent, Gordon; Bernstein, Steven R.; Hanna, William, 1910-2001; Barbera, Joseph; Potamkin, Buzz (Warner Home Video, 2003)
Scooby-Doo and Shaggy travel to Arabia to become the Caliph's royal food tasters. But they bite off more than they can chew and are forced to run for their lives.